Distinct Fates of Chemokine and Surrogate Molecule Gradients: Consequences for CCR7-Guided Dendritic Cell Migration - Artinger, Marc; Gerken, Oliver J.; Purvanov, Vladimir; Legler, Daniel F. (Frontiers in Immunology, 2022)
Chemokine-guided leukocyte migration is a hallmark of the immune system to cope with invading pathogens. Intruder confronted dendritic cells (DCs) induce the expression of the chemokine receptor CCR7, which enables them to sense and migrate along chemokine gradients to home to draining lymph nodes, where they launch an adaptive immune response. Chemokine-mediated DC migration is recapitulated and intensively studied in 3D matrix migration chambers. A major caveat in the field is that chemokine gradient formation and maintenance in such a 3D environment is generally not assessed. Instead, fluorescent probes, mostly labelled dextran, are used as surrogate molecules, thereby neglecting important electrochemical properties of the chemokines. Here, we used site-specifically, fluorescently labelled CCL19 and CCL21 to study the establishment and shape of the chemokine gradients over time in the 3D collagen matrix. We demonstrate that CCL19 and particularly CCL21 establish stable, but short-distance spanning gradients with an exponential decay-like shape. By contrast, dextran with its neutral surface charge forms a nearly linear gradient across the entire matrix. We show that the charged C-terminal tail of CCL21, known to interact with extracellular matrix proteins, is determinant for shaping the chemokine gradient. Importantly, DCs sense differences in the shape of CCL19 and CCL21 gradients, resulting in distinct spatial migratory responses.